Malaysia crime mapping: GIS Dashboard / Puteri Nur Syafiqah Megat Omar Azahari - Megat Omar Azahari, Puteri Nur Syafiqah (2023)
Crime mapping indicates an important contribution to the societies and securities forces to develop an effective and efficient solution spatially to enforcing the geographically distribution of crime prevention. The increment usage of social media nowadays such as Facebook, Twitter, and others social media platform could be useful to this endeavor on developing the suitable crime mapping platform. Thus, the aim of this study is to accommodate the systematic criminal statistical study involved the visualization and organized spatial data using dashboard. The objectives of this study are to i) prepare types and number of crime cases in Malaysia acquire through crowdsourcing approach and ii) developed informative GIS dashboard for crime cases in Malaysia. The focused area is carried out in Malaysia. Four parameters such as the types of crime, date range of crime, location of hotspot area, and statistics of crime from 2015 until 2020 that will be used in this study. The methodology of this research consists of main four phases which are i) data acquisition and preparation, ii) data processing, iii) design and development and i) deployment. This study helps to demonstrates on how the crime mapping dashboard aid the prevention of crime in hotspot area in Malaysia using the proposed dashboard.